2014
DOI: 10.1371/journal.pone.0092649
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Secretion by Astrocytes Is Dynamically Regulated by PI3K-mTOR-Calcium Signaling

Abstract: After contusion spinal cord injury (SCI), astrocytes become reactive and form a glial scar. While this reduces spreading of the damage by containing the area of injury, it inhibits regeneration. One strategy to improve the recovery after SCI is therefore to reduce the inhibitory effect of the scar, once the acute phase of the injury has passed. The pleiotropic cytokine interleukin-6 (IL-6) is secreted immediately after injury and regulates scar formation; however, little is known about the role of IL-6 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 56 publications
3
24
0
Order By: Relevance
“…The vesicular release of IL‐6 from spinal cord is calcium dependent (Codeluppi et al . ), and the time course of the IL‐6 release above implies the signaling mechanisms are distinct from those involved in transcriptional up‐regulation. While the increased expression of IL‐6 would provide more IL‐6 for release upon later stimulation, this complex positive feedback pathway was not investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vesicular release of IL‐6 from spinal cord is calcium dependent (Codeluppi et al . ), and the time course of the IL‐6 release above implies the signaling mechanisms are distinct from those involved in transcriptional up‐regulation. While the increased expression of IL‐6 would provide more IL‐6 for release upon later stimulation, this complex positive feedback pathway was not investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…3g). Cytokine release in many cell types is mediated by increases in intracellular calcium; for example, the release of IL-6 from spinal cord astrocytes is calcium dependent (Codeluppi et al 2014). To confirm optic nerve head astrocytes experience a rise in calcium upon swelling, levels were monitored with indicator Fura-2.…”
Section: Il-6 Released From Optic Nerve Head Astrocytesmentioning
confidence: 99%
“…These results indicate that the inhibitory effect of mTOR signaling was not signi cantly different in response to similar visual cues. Recent studies have suggested that mTOR signaling may be involved in the initiation of pain perception [15,19], which could effectively reduce chronic pain through inhibition of mTOR [43,44]. However, the amount of research on how pain is controlled regarding the regulation of mTOR is still insu cient.…”
Section: How Can Mtor Inhibition Reduce Brain Activities Of Chronic Pmentioning
confidence: 99%
“…The activation of mTOR regulates protein synthesis and in uences a wide range of physiological and pathological states by phosphorylating downstream effectors [12,17,18]. In this study, the mTOR selective inhibitors known as Torin1 [19,20] and XL388 [21] were used to modulate the mTOR regulator. Each agent has highly potent and ATP-competitive mTOR inhibitory effects.…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K/Akt pathway is of particular interest because of its known role in modulating autophagic clearance of A␤ in neurons (58) and because of its known ability to inhibit M1 macrophage polarization (59), which is linked to expression of scavengers receptors, including CD36 (60). Further, this pathway is important to astrocyte immune function, as it is involved in regulating astrocyte viability, migration, autophagy, and production of cytokines and inflammatory mediators (61)(62)(63)(64)(65).…”
Section: Heme and Hemoglobin Modulate The Pi3k/akt Pathwaymentioning
confidence: 99%